A debreceni Stomatologiai Klinika története Adler Péter professzor vezetése alatt (1946–1979) - Kelentey, Barna (Gerundium, 2019)
History of the Stomatology Clinic in Debrecen under the Leadership of Professor Péter Adler (1946–1979). With the approaching front of the 2nd World War in October 9, 1944, Professor András Csilléry head of the Stomatology Clinic left Debrecen because of his political views, so the institution remained without a leader until 17th November. Thereafter as a substitute, trainees then Stefánia Morvay Assistant Lecturer under the supervision of Professor Gyula Verzár was the head. From June 20, 1946, Péter Adler was assigned to the lead, which was one of the longest leading positions of the Faculty of Medicine since he was director of the clinic until July 1, 1979. Péter Adler graduated from the University of Vienna, where he specialized in the field of Dentistry and worked at the Department of Orthodontics at the Polyclinic of Vienna, while in spring 1939 he had to return home for political reasons. During the war he worked as a translator and then assigned to forced labor, and after the war, he was placed to the Stomatology Clinic in Debrecen. From 1948 he worked as a chief clinician, in 1952 he became candidate of sciences (CSc), and in 1953 he was appointed as a university professor. He received Doctor of Science (DSc) degree in 1957. He was a member of the editorial board of several foreign professional journals, he was accepted by several international editorial boards, wrote several textbooks. He translated two books written by others into German. He was chairman of the Association of Hungarian Dentists and Editor-in-Chief of the Stomatologica Hungarica. The main topics of the research at the Stomatology Clinic are: examination of hypersensitivity to dental anesthetics, clarification of many details of caries epidemiology, proof of the protective effect of fluoride against caries. Under his leadership there was a dynamic scientific work on the Stomatology Clinic, proven by the fact that between 1945–1980 12 books, 487 publications, book chapters and monographs appeared, which was unique among similar national institutions. He lay down the fundaments of the dental education in 1976 and contributed the architectural and professional requirements of the new Stomatology Clinic in 1981.